Respostas
respondido por:
2
Aplicando o teorema de Tales, temos:
12x + 12y = 80
3x + 3y = 20
Sendo y = 3x, temos:
3x + 9x = 20
12x = 20
x =
Se y = 3x
y = 3.
y = 5
12x + 12y = 80
3x + 3y = 20
Sendo y = 3x, temos:
3x + 9x = 20
12x = 20
x =
Se y = 3x
y = 3.
y = 5
respondido por:
2
Aplicando o teorema de Tales, temos: temos:
12x + 12y = 80
3x + 3y + 20
Sendo y = 3x, temos:
3x + 9x + 20
12x = 20
x =
Se y = 3x
y = 3
y = 5
Espero ter te ajudado e bons estudos!!
:)
12x + 12y = 80
3x + 3y + 20
Sendo y = 3x, temos:
3x + 9x + 20
12x = 20
x =
Se y = 3x
y = 3
y = 5
Espero ter te ajudado e bons estudos!!
:)
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás